Paramyxovirus infection driven by heteromultivalent sialoglycotope binding - Xuesheng Wu; Mengying Liu; Laura Blekkenhorst; Mare H. L. Verbruggen; Nancy N. M. P. Schuurman; Lemeng Chao; Jun Yang Ong; Tom Wennekes; Laura L. A. van Dijk; Rory D. de Vries; Frank J. M. van Kuppeveld; Henrik Clausen; et al. (Proceedings of the National Academy of Sciences, 2026)
Sialic acids (Sia) on glycoproteins and glycosphingolipids act as receptors for many respiratory viruses, including human influenza A viruses and respiroviruses, which typically bind to α2-6- and α2-3-linked Sia (2-6Sia and 2-3Sia), respectively. In view of this binding discrepancy and as the exact sialoglycoconjugates supporting respirovirus infection remain unclear, we assessed the receptor requirements for infection and binding of several respiroviruses and avian Newcastle disease virus (NDV). To this end, we employed a library of isogenic HEK293 cells displaying defined sialoglycoconjugates. Respirovirus infection was shown to strictly depend on 2-3Sia, with a preference for the terminal Siaα2-3Galβ1-4GlcNAc sialoglycotope regardless of the underlying glycoconjugate structure, whereas NDV showed a broader sialoglycotope usage. Notably, 2-6Sia enhanced respirovirus infection in low 2-3Sia contexts via heteromultivalent surface binding, which resulted in prolonged virus–receptor interactions. This heteromultivalent binding is expected to aid respirovirus infection of the 2-6Sia-rich human upper respiratory tract.